Familial Mediterranean fever type 2 with heterozygous mutations of E148Q and M694I in a Japanese patient with progressive systemic AA amyloidosis. (2nd January 2019) - Ito, Mayumi; Nobata, Hironobu; Imai, Hirokazu; Yoshino, Masabumi; Banno, Shogo; Ito, Yasuhiko; Ito, Hideaki; Kishida, Dai
Abstract: A 44-year-old Japanese woman showing rapidly progressive amyloid A (AA) systemic amyloidosis died due to multiple organ failure on hospital day 18. No underlying disorder for systemic AA amyloidosis was revealed on autopsy. Familial Mediterranean fever (FMF) type 2, which usually lacks clinical symptoms with amyloidosis as the first or sole manifestation of the disease, was suspected because of an absence of recurrent fever, serositis, or family history. Analysis of the Mediterranean Fever (MEFV) gene revealed heterozygous mutations of E148Q in exon 2 and M694I in exon 10. We finally diagnosed FMF type 2. FMF type 2 should be considered in AA-type amyloidosis of unknown origin even in the absence of systemic symptoms.